Teknologi Penangkapan Rajungan (Portunus pelagicus spp.) Ramah Lingkungan dengan Bubu Kubah di Kabupaten Aceh Barat Provinsi Aceh - Hafinuddin Hafinuddin; Edwarsyah Edwarsyah (Universitas Teuku Umar, 2017)
Fishermen of West Aceh District is still using a tool of unfriendly for environment namely mini trawl for blue swimming crab (Portunus pelagicus spp) fishing, so that it will impact the ecosytem of the sea and the damage to the fish resources such as blue swimming crab. For that reason, there needs to be an alternative of eco-friendly fishing technology to catching blue swimming crab and replace fishing gear unfriendly for environment i.e. mini trawl and exposing the blue swimming crab fishing is as main activity in West Aceh District where Ujong Baroh Village as pilot projetc location for this activity. The community service program has carried out with IbM activity (Ipteks bagi Masyarakat). The activity was done on February – Agustus 2017, where education, practice and accomponiment was used as methods. IbM program is expected to increase skill and business managerial as well as improving the economic situation of the coastal communities.